2018
DOI: 10.1109/tmbmc.2019.2895815
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Based Molecular Communication With Limited Molecule Production Rate

Abstract: This paper studies the impact of a transmitter's molecule generation process on the capacity of a concentration based Molecular Communication (MC) system. Constraints caused by the molecule generation process affect the availability of the molecules at the transmitter. The transmitter has a storage of molecules, and should decide whether to release or save the currently produced molecules. As a result, the MC system has conceptual connections with energy harvesting systems. In this paper, we consider two scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…However, at dimensions in question, without any replenishment, these reservoirs will inevitably deplete, rendering the nanomachine functionally useless in terms of MC. Moreover, the replenishment rate of transmitter reservoirs has a direct effect on achievable communication rates [16], [17]. Possible theoretically proposed scenarios for reservoir replenishment include local synthesis of IMs, e.g., use of genetically engineered bacteria whose genes are regulated to produce the desired transmitter proteins [18], as well as employment of transmitter harvesting methods [19].…”
Section: A Design Requirements For Mc-txmentioning
confidence: 99%
“…However, at dimensions in question, without any replenishment, these reservoirs will inevitably deplete, rendering the nanomachine functionally useless in terms of MC. Moreover, the replenishment rate of transmitter reservoirs has a direct effect on achievable communication rates [16], [17]. Possible theoretically proposed scenarios for reservoir replenishment include local synthesis of IMs, e.g., use of genetically engineered bacteria whose genes are regulated to produce the desired transmitter proteins [18], as well as employment of transmitter harvesting methods [19].…”
Section: A Design Requirements For Mc-txmentioning
confidence: 99%
“…On the molecular level, energy-aware algorithms can be used for efficient coordination and movement EH nanonetworks, e.g., engineered bacteria tracking and eliminating harmful targets in the human body (Islam et al, 2020). Since the molecules harvested for energy generation can also transport information, the EH process directly governs data transmissions (Bafghi et al, 2018). Other approaches, such as feedback control, are also promising for energy-aware MC, especially in diffusion-based information transfer (Musa et al, 2020).…”
Section: Energy-aware Communicationsmentioning
confidence: 99%
“…In addition, considering that the molecule generator in the source has a limited productivity, the concentrations is hence assumed to satisfy an average constraintc ∈ [c L , c H ]. Note that this assumption has been adopted in the previous works [13] and [27] to make the model more realistic.…”
Section: B System Modelmentioning
confidence: 99%
“…As an upper bound of the channel capacity C defined in (13), C FB can be used to evaluate the tightness of C IID approximating to the channel capacity C. It can be concluded that C IID provides a tight lower bound of C.…”
Section: Achieving Ratesmentioning
confidence: 99%
See 1 more Smart Citation